The Glucagon-Like Adipokinetic Hormone in Drosophila melanogaster – Biosynthesis and Secretion - Hughson, Bryon N. (Frontiers in Physiology, 2021)
Metabolic homeostasis requires the precise regulation of circulating sugar titres. In mammals, homeostatic control of circulating sugar titres requires the coordinated secretion and systemic activities of glucagon and insulin. Metabolic homeostasis is similarly regulated in Drosophila melanogaster through the glucagon-like adipokinetic hormone (AKH) and the Drosophila insulin-like peptides (DILPs). In flies and mammals, glucagon and AKH are biosynthesized in and secreted from specialized endocrine cells. KATP channels borne on these cells respond to fluctuations in circulating glucose titres and thereby regulate glucagon secretion. The influence of glucagon in the pathogenesis of type 2 diabetes mellitus is now recognized, and the precise mechanism that regulates glucagon secretion was reported nearly a decade ago. Ongoing efforts to develop D. melanogaster models for metabolic syndrome must build upon this seminal work. These efforts make a critical review of AKH physiology timely. This review focuses on AKH biosynthesis and the regulation of glucose-responsive AKH secretion through changes in CC cell electrical activity. Future directions for AKH research in flies are discussed, including the development of models for hyperglucagonemia and epigenetic inheritance of acquired metabolic traits. Many avenues of AKH physiology remain to be explored and thus present great potential for improving the utility of D. melanogaster in metabolic research.